Soil organic matter increase and fruit yield of mango trees in Luvisols of Campeche, México - Medina Méndez, Juan; Volke Haller, Víctor; Galvis Spínola, Arturo; Cortés Flores, José Isabel; Santiago Cruz, Ma. de Jesús (Agronomía Mesoamericana, 2017)
<!--[if gte mso 9]> 0 0 1 190 1051 Revista Agronomía Mesoamericana 8 2 1239 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES-AR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> The objective of this study was to determinate the effect of increasing soil organic matter on fruit yield of mango trees under irrigated conditions, in Luvisols of Campeche State, Mexico. In every 48 commercial orchards and five sites under natural forest vegetation, soil samples were taken in order to determine physical and chemical properties. Furthermore, in orchards sites, leaf sampling was carried out, and data on orchard management practices and fruit yield also were registered. The collected data was analyzed using regression analysis. From soil organic matter content in continues sole maize cropping system under rainfed agriculture or irrigated vegetables, soil organic matter content in mango orchards increased from 3.26% in a period since 1 to 5 years to 5.66% after a period of 16 to 30 years. In soil under natural forest vegetation, organic matter content was 5.36%. Increasing soil organic matter content and tree age, fruit yield increased by 9.5 t/ha after 26 to 30 years under cultivation. <!--EndFragment-->